Destination London: The Expansion of the Visitor Economy - Andrew Smith; Anne Graham (University of Westminster Press, 2019)
London is one of the world's most popular destinations and visitors contribute approximately 14.9 billion of expenditure to the city every year. Its tourism and events sectors are growing and over the last few years London has received more visitors than ever before. However, detailed accounts of the city's visitor economy are conspicuously absent. This book analyses how the capital is developing as a destination through the expansion of tourism and events into new urban spaces. The book outlines how parts of London not previously regarded as tourist territory are now subject to the visitor gaze with tourism spreading beyond established central zones into peripheral, suburban and residential areas - in part propelled by a big rise in peer to peer accommodation use. Simultaneously, London's airports and sports stadiums and their surrounds are becoming destinations in their own right. New vantage points have been created, allowing tourists to explore the city: from above, at night-time or through tours given by the homeless; via the opening up of the River Thames; or through the transformation of local parks into eventscapes. The book explores these trends and shows how urban destinations expand. In doing so, it enhances our understanding of London and highlights the growing significance of tourism and events in global cities.
Keywords: 300; development; overtourism; visitors; urban; London; tourism